The Fashion Industry Terminology and Linguistic Means of Expression in Modern Russian, Chinese and English - Lobanova, Tatiana Nikolaevna; Badretdinova, Albina Abdulbarievna; Dubyaga, Anastasiya Mikhailovna (Филология: научные исследования, 2025)
The research subject is fashion industry terminology and linguistic means of expression within the media discourse in the materials of glossy press and online fashion journalism in three languages (English, Chinese and Russian). The study of the terminology of the fashion industry, as well as the functioning of language in the above-mentioned materials is the most urgent direction of modern fundamental and applied linguistics. The aim of the article is to study English, Russian and Chinese terminology of the fashion industry. The aim of the article is a comprehensive study of English, Russian and Chinese terminology of the fashion industry. The article also intends to study linguistic means of expression in media texts on fashion industry issues with the involvement of a functional approach (in the media discourse of glossy press and fashion journalism). The main content is concentrated around the analysis of the concepts of ‘term’, ‘linguistic means of expression’, ‘fashion industry’, ‘fashion journalism’ from the linguistic point of view. The research methods are definitional analysis, discourse analysis, translation and linguocultural analysis, etc. The text of a glossy magazine and a digital media text serve as the basic unit of analysis in the study of modern Chinese and English-language media. The scientific novelty of the research is due to the subject of the study and the lack of modern research in the field of online journalism in the aspect of studying the formation of fashion industry terminology and linguistic means of expression in the construction of the image of beauty in the media (in glossy magazines and digital products-analogues).